Beyond borders Web globalization strategies - Yunker, John (Safari tech books online., 2003)
Companies know that globalizing their web sites will produce exponential revenue growth - Web Globalization Strategies: Beyond Borders tells web developers how to do it. By 2003, the US will account for less than one-third of the worldwide Internet user-base of 602 million. This book illustrates step-by-step measures to take to globalize any web site for almost any country in the world, while presenting spotlights on real companies who have globalized their sites and the benefits they've received. Most executives know they want to reach a global market but have no idea what obstacles they face. The web globalization process is complex, constantly evolving, and the languages themselves can be highly intimidating. This book will provide the reader with the understanding and "best practices" necessary to successfully manage a Web globalization strategy. Crammed with useful facts, tips, and ideas, this book will offer step-by-step advance on every aspect of web development, both technical and non-technical. Offers practical, in-depth information on such hard-to-research topics as online revenue models, online marketing options, site traffic analyses, usability testing, community building, legal issues, cost projections, and project management.